Quality Management System Program of in Vitro/in Vivo Test Facility of Boron Neutron Capture Therapy at Kartini Research Reactor - Widarto Widarto; Isman Mulyadi Tri Atmoko; Gede Sutresna Wijaya (Indonesian Journal of Physics and Nuclear Applications, 2016)
The quality manajement system program of in vitro / in vivo test facility of  Boron Neutron Capture Therapy (BNCT) methode as quality assurance requirement for utilization of radial pearcing beamport of Kartini research have been done.  Identification and management of technical specification and parameters meassurement of to the radial piercing beamport have been determined for preparing in vitro / in vivo test facility. The parameters are epithermal neutron flux is  9,8243E+05  n cm-2 s-1and  thermal neutron flux is 3,0691E+06 n cm-2 s-1, radiation shielding of parafin,  dimension and size  of piercing radial and instrumentatin and control system for automatic transfer of in vitro / in vivo samplels have been documented. Management system of the documents for fullfil  basic guidance to perform working job of in vitro / in vivo at the piercing radial beamport of Kartini Research Reactor in order purpose utilization of the reactor  for safety worker of the radiation area, society  and invironment beeing safely